Endgame, Its Opening and Closing Style: A Conversation Analytic Study - Zasqia Damai Aulia Shakti (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
Conversation Analysis (CA) is crucial in discourse studies, focusing on everyday interactions. This study examines the conversational styles in the Indonesian talk show Endgame, hosted by Gita Wirjawan. Previous research on Indonesian talk shows has primarily explored speech acts and pragmatic aspects, with little emphasis on openings and closings. This study addresses that gap by applying CA to analyze these segments in